2012
DOI: 10.4314/agrosh.v12i1.2
|View full text |Cite
|
Sign up to set email alerts
|

Empirical Analysis Of Agricultural Production And Inflation Rate In Nigeria (1970- 2006)

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 3 publications
1
4
0
Order By: Relevance
“…In this case, the valuation of GDPA would be high. This finding is in conformity with Olatunji et al (2012) that there was direct relationship between agricultural output change and inflation rate in Nigeria between 1970 and 2006. Similarly, Oyinbo and Rekwot (2014) found that there was a unidirectional causality from inflationary trend to agricultural productivity.…”
Section: Optimal Lag Selectionsupporting
confidence: 91%
“…In this case, the valuation of GDPA would be high. This finding is in conformity with Olatunji et al (2012) that there was direct relationship between agricultural output change and inflation rate in Nigeria between 1970 and 2006. Similarly, Oyinbo and Rekwot (2014) found that there was a unidirectional causality from inflationary trend to agricultural productivity.…”
Section: Optimal Lag Selectionsupporting
confidence: 91%
“…In an effort to curb the incidence of poverty as well as food insecurity in the country, successive governments embarked on various policies and programmes aimed at boosting agricultural production (Olatunji et al, 2012). This is because agriculture remains the major source of livelihood of majority of the rural poor in the country.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard an empirical investigation of the determinants of inflation is essential. The high inflation rate has become a major concern because poverty rate has increased (Olatunji, Omotesho, Ayinde and Ayinde, 2010).…”
Section: Literature Review 21 Theoretical Considerations and Empirica...mentioning
confidence: 99%